Effect of medium-chain triacylglycerol and carbohydrate ingestion during exercise on substrate utilization and subsequent cycling performance - Jeukendrup, A. E.; Thielen, J. J.; Wagenmakers, A. J.; Brouns, F.; Saris, W. H. (The American Journal of Clinical Nutrition, 1998)
The aim of this study was to investigate the effect of medium-chain triacylglycerol (MCT) ingestion during exercise on subsequent time- trial cycling performance. Seven well-trained cyclists performed four exercise trials consisting of 2 h at 60% of maximal oxygen uptake followed by a simulated time trial (ie, completion of a preset amount of work as fast as possible) of approximately 15 min duration. During the trials, subjects ingested 1) a 10% carbohydrate solution (CHO; 170 +/- 6 g glucose), 2) a 10% carbohydrate electrolyte with 5% MCT solution (CHO + MCT; 85 +/- 3 g MCT), 3) a 5% MCT solution, or 4) artificially colored and flavored water (placebo). Neither CHO nor CHO + MCT ingestion had any effect on performance compared with placebo ingestion, whereas ingestion of MCT had a negative effect on performance. Average work rates during the time trial were 314 +/- 19, 314 +/- 13, and 312 +/- 18 with CHO, CHO + MCT, and placebo, respectively, and was 17-18% lower in the MCT trial (263 +/- 22 W). In addition, compared with placebo ingestion, MCT ingestion had no effect on total rates of fat or carbohydrate oxidation, nor did it affect exogenous or endogenous carbohydrate utilization. The negative effect of MCT ingestion was associated with increased gastrointestinal complaints (ie, intestinal cramping). These data suggest that large amounts of MCTs (85 g) ingested during prolonged submaximal exercise may provoke gastrointestinal problems leading to decreased exercise performance.